“Ummat” sebagai Upaya Meningkatkan Hasil Belajar Matematika Siswa Kelas VIA SDN Kalibanteng Kidul 01 Semarang - Nur Rakhmat (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Learning is a continuous business process in order to get optimal results. Therefore, learning requires sharing creative ways to achieve the best results. As happened at SD Negeri Kalibanteng Kidul 01 Semarang, especially when studying mathematics, the learning outcomes obtained by students were not maximized, that is, there were still 24 out of 40 students who scored below the KKM set, namely 70. This means that only 16 students scored above KKM. Apart from being caused by mathematics being a difficult subject, the learning process is still perfunctory, still conventional and only in class and has not utilized learning media optimally. After going through several processes, we used "UMMAT" as an effort to improve math learning outcomes. And it has been proven that "UMMAT", which is a traditional game-based learning media by applying a cooperative learning approach, can be a solution to overcome the difficulties of math problems. Of the only 16 students who passed above the KKM, after using "UMMAT" there were 36 students who scored above the KKM. And there was an increase in learning outcomes from 16 students or 40% of students who passed the KKM to 36 students or 90% of students after "UMMAT" was used. This means that there is an increase of 50% in student mathematics learning outcomes after using "UMMAT".